Radiofrequency ice dielectric measurements at Summit Station, Greenland - Aguilar, Juan Antonio; Allison, Patrick; Curtis-Ginsberg, Zach; Dasgupta, Paramita; de Kockere, Simon; de Vries, Krijn D.; Deaconu, Cosmin; DuVernois, Michael A.; Eimer, Anna; Glaser, Christian; Hallgren, Allan; Hallmann, Steffen; et al. (Soc., 2023)
We recently reported on the radio-frequency attenuation length of cold polar ice at Summit Station, Greenland, based on bi-static radar measurements of radio-frequency bedrock echo strengths taken during the summer of 2021. Those data also allow studies of (a) the relative contributions of coherent (such as discrete internal conducting layers with sub-centimeter transverse scale) vs incoherent (e.g. bulk volumetric) scattering, (b) the magnitude of internal layer reflection coefficients, (c) limits on signal propagation velocity asymmetries (‘birefringence’) and (d) limits on signal dispersion in-ice over a bandwidth of ~100 MHz. We find that (1) attenuation lengths approach 1 km in our band, (2) after averaging 10 000 echo triggers, reflected signals observable over the thermal floor (to depths of ~1500 m) are consistent with being entirely coherent, (3) internal layer reflectivities are ≈–60–70 dB, (4) birefringent effects for vertically propagating signals are smaller by an order of magnitude relative to South Pole and (5) within our experimental limits, glacial ice is non-dispersive over the frequency band relevant for neutrino detection experiments.